Molecular Characterization of Cytokinin Response Regulator ARR21 in Arabidopsis Seed Development - Sujeong Jeong; Inyoung Kim; Hyun Uk Kim (Plant Direct)
ABSTRACT The role of cytokinin among plant hormones in seed development remains largely unknown. The Arabidopsis response regulator 21 (ARR21) is one of the cytokinin response regulators and a Type‐B ARR with a nuclear localization signal and a GARP motif similar to the MYB‐like DNA‐binding domain. ARR21‐sGreen fluorescent protein (GFP) signals were localized within the nucleus, and ARR21 showed the highest expression levels in developing seeds. In addition, histochemical analysis revealed ARR21 expression in the silique coats, chalazal seed coat, chalazal endosperm, and throughout the developing seed at 6 days after pollination. Two independent mutants were generated using the CRISPR/Cas9 system: arr21‐3 (51 bp in‐frame deletion) and arr21‐4 (2 bp insertion). The seed size and weight of the arr21 mutants decreased by an average of 10.7% and 37%, respectively, compared to the wild‐type (WT). In arr21 mutants, the cotyledon length of embryos and the size of seed coat cells were reduced. Seed‐specific overexpression of ARR21 in arr21‐4 restored the seed length to WT levels. This study suggests that ARR21 regulates seed size by functioning in the chalazal endosperm and embryo, thereby providing insights into the role of cytokinin in seed development.